2007
DOI: 10.1063/1.2710273
|View full text |Cite
|
Sign up to set email alerts
|

Vortex shedding from a circular cylinder near a moving ground

Abstract: The flow and force characteristics have been experimentally investigated of a circular cylinder with an aspect ratio of 8.33, with and without end-plates, placed near and parallel to a moving ground, on which substantially no boundary layer developed to interfere with the cylinder. Mean drag and lift measurements, surface oil flow visualization, and particle image velocimetry ͑PIV͒ measurements were carried out at two upper-subcritical Reynolds numbers of 0.4 and 1.0ϫ 10 5 ͑based on the cylinder diameter d͒ to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
34
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 23 publications
7
34
0
Order By: Relevance
“…Strongly increasing region: Comparing with Nishino et al (2007), we have more data for very small gap ratios, as shown in Fig. 16 (b).…”
Section: Lift Coefficientmentioning
confidence: 75%
See 3 more Smart Citations
“…Strongly increasing region: Comparing with Nishino et al (2007), we have more data for very small gap ratios, as shown in Fig. 16 (b).…”
Section: Lift Coefficientmentioning
confidence: 75%
“…Zdravkovich (1985) found that the lift coefficient is governed by the gap to diameter ratio for a cylinder near a plane wall. Nishino et al (2007) found a rapid increase of the lift coefficient as the gap to diameter ratio decreases to less than about 0.5.…”
Section: Lift Coefficientmentioning
confidence: 86%
See 2 more Smart Citations
“…In stationary bluff bodies, there is a critical gap between the body and the ground below which vortex shedding is suppressed [23]. While a similar effect can be expected of airfoils, the change in ride height with time will undoubtedly introduce an additional constraint to the flow.…”
mentioning
confidence: 92%